Screening of biomarkers in acute radiation enteritis based on microbiome and clustering methods - Chenying Ma; Xiaoting Xu; Songbing Qin; Juying Zhou (BMC Microbiology)
Abstract Background Radiation enteritis (RE) is a common complication of radiotherapy for abdominal and pelvic tumors, adversely affecting treatment outcomes and patients’ quality of life. Gut microbiome alterations may contribute to RE development, but the underlying pathogenic factors are not fully understood. This study aimed to characterize the intestinal microbial changes associated with RE and severe acute radiation enteritis (SARE) and to identify predictive biomarkers. Methods We enrolled 50 cervical cancer patients undergoing radiotherapy and 15 healthy women (controls). Stool samples were collected at the baseline and during weeks 2, 4, and 6 of radiotherapy, and then analyzed using 16 S rDNA sequencing and bioinformatics. Results Although the Bacteroidetes/Firmicutes (B/F) ratio was higher in patients with RE or SARE, it alone could not predict these conditions. Three enterotypes were identified based on dominant genera: Blautia (enterotype 1), Escherichia-Shigella (enterotype 2), and Faecalibacterium (enterotype 3). A decrease in Blautia and an increase in Escherichia-Shigella and Faecalibacterium were correlated with RE and SARE. Univariate logistic regression revealed that the Faecalibacterium enterotype at the baseline was associated with a 4.4-fold higher risk of developing SARE (odds ratio 5.400; P = 0.017). The Escherichia-Shigella enterotype was also linked to increased SARE incidence. Conclusion These findings suggest that while single bacterial genera or the B/F ratio are insufficient predictors, enterotype classification may serve as a potential biomarker for predicting SARE in patients undergoing radiotherapy.